Factors Influencing Human Resource Performance in Riau Prison Building Construction Projects in 2021-2022 - Poniman; Suherman, Hendra; Zuherna (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aimed to identify, analyze human resource performance factors in prison building construction projects in Riau and provide recommendations to find the dominant factors of human resource performance in building construction projects in Riau. The population in this study was the Public Works Agency (KPU), supervisory consultants, contractors that execute the building construction projects in Riau. Quantitative method was applied in this study. The data was collected through questionnaires, while data processing was carried out by SPSS (Statistical Package for the Social Sciences). The results of this study showed that there are 8 human resource performance factors, such as work ability, work environment, discipline, compensation, experience, competence, motivation, and loyalty. From data processing, 11 new factors were formed becoming the dominant factors, specifically professional and responsible factors. These can be seen in the Total Variance Explained table which show the largest percent of variance are professionalism and responsibility factors with a percentage extraction level which is 14.518%. Of the 8 human resource performance factors, the most dominant is professionalism and responsibility with variables from loyal variables in the application of company rules, ability to comply with project management regulations, responsibility for the work carried out, able to work optimally, effectively and efficiently, and give full time, energy, and mind to the completion of work.